2019
DOI: 10.1002/maco.201810451
|View full text |Cite
|
Sign up to set email alerts
|

The influence of NaCl and CaCl2 induced high temperature corrosion on the aqueous corrosion resistance of stainless steels

Abstract: The corrosion resistance of the steel grades 1.4509 and 1.4301 against sodium and calcium chloride, at 650 and 750 °C is investigated by means of cyclic exposure tests (CETs) in dry air. The formation of chromates as well as volatile metal chlorides and oxychlorides leads to non‐protective oxide scales on both steel grades. At 650 and 750 °C and in presence of a salt layer the alloy 1.4301 shows a higher corrosion resistance than the material 1.4509. At 750 °C and in presence of salt, the surface of the steel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…However, when temperatures rise and a corrosive environment, for example NaCl, KCl or other salts are present, the chromium oxide is no longer protective. Cao et al [5] reported that while the mass gain during 20 h long exposure at 600°C remain almost zero, in the presence of NaCl it was approximately 7 mg/cm 2 . In addition, the difference between the coefficients of linear thermal expansion of oxides and metals causes the voluminous oxides to flake off when temperatures change [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when temperatures rise and a corrosive environment, for example NaCl, KCl or other salts are present, the chromium oxide is no longer protective. Cao et al [5] reported that while the mass gain during 20 h long exposure at 600°C remain almost zero, in the presence of NaCl it was approximately 7 mg/cm 2 . In addition, the difference between the coefficients of linear thermal expansion of oxides and metals causes the voluminous oxides to flake off when temperatures change [6].…”
Section: Introductionmentioning
confidence: 99%
“…One of not often studied areas is automotive exhaust systems, which operate at high temperatures with peaks of up to 1000°C near the engine [1]. In addition to high temperatures, the presence of salts from winter road de-icing accelerates the corrosion of exhaust components and leads to their degradation [2]. In recent decades, stainless steels have partially replaced low alloy steels in exhaust systems due to their longer life and better appearance [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To make these plants economically viable, there is a need to focus on the corrosion problem, which is relatively more aggressive due to the presence of chlorine in the waste. The presence of chlorine at high temperature results in a highly corrosive working environment mainly due to the “oxychlorination” reactions based on the “active oxidation” mechanism . In Ni–Cr‐based coatings, the preferential formation of an oxide of chromium is likely as compared to nickel, which has a comparatively lesser affinity for oxygen and nickel oxide is less stoichiometric than chromium oxide.…”
Section: Introductionmentioning
confidence: 99%